Theology of Harmony in the Indonesian Context: Azyumardi Azra's Perspective - Zakia Aini (Islamic Thought Review, 2025)
This study examines Azyumardi Azra’s perspective on the theology of harmony in the Indonesian context, particularly in addressing the dynamics of religious plurality and conflict. In the last two decades, Indonesia has witnessed serious cases of religious conflict, such as the Ambon conflict (1999–2002) and various sectarian tensions within Islam itself. For Azra, the theology of harmony reaches its culmination in the acceptance and practice of Pancasila as the state ideology, which provides a unifying foundation for different religions in Indonesia. This research employs a library study and character study approach to explore Azra’s ideas, focusing on his concept of Islamic inclusivism. The findings indicate that Azra situates harmony on two levels: doctrinal, which emphasizes the universality of Islamic teachings, and historical, which acknowledges the lived experiences of Indonesian Muslims in a plural society. Furthermore, he highlights the importance of local wisdom, such as the Minangkabau philosophy “dima bumi dipijak, di situ langik dijunjuang” (where the earth is stepped on, there the sky is upheld), which promotes contextual inclusivism without sacrificing core faith and practices. Thus, Azra’s theology of harmony offers a constructive framework for interreligious coexistence and national integration in Indonesia.